Low Noise Amplifier at 5.8GHz with Cascode and Casc aded Techniques Using T-Matching Network for Wireless Ap plications - Ibrahim A.B; Abdul Rani Othman; Hussain M.N; Othman A.R; Johal M.S (International Journal of Electrical and Computer Engineering (IJECE), 2011)
This project present a design of a 5.8 GHz low noise amplifier (LNA) design with cascode and cascaded techniques using T-matching network applicable for IEEE 802.16 standard. The amplifier use FHX76LP Low Noise SuperHEMT FET. The LNA designed used T-matching network consisting of lump element reactive element at the input and the output terminal. The cascode and cascaded low noise amplifier (LNA) produced gain of 36.8dB and noise figure (NF) at 1.3dB. The input reflection (S11) and output return loss (S22) are -11.4dB and -12.3dB respectively. The bandwidth of the amplifier is more than 1GHz. The input sensitivity is compliant with the IEEE 802.16 standards.DOI:http://dx.doi.org/10.11591/ijece.v1i1.63